If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -4 + b = 44 Reorder the terms: -4 + 2b + b = 44 Combine like terms: 2b + b = 3b -4 + 3b = 44 Solving -4 + 3b = 44 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3b = 44 + 4 Combine like terms: -4 + 4 = 0 0 + 3b = 44 + 4 3b = 44 + 4 Combine like terms: 44 + 4 = 48 3b = 48 Divide each side by '3'. b = 16 Simplifying b = 16
| 5x-(3x+5)=5x-41 | | (2x+12)(x-1)=0 | | x^2-36x-162=0 | | 14t=4(1-5t) | | -5+3x+7= | | 44-(2b-4)=b | | 2x^2-36x-162=0 | | x-1/5-x=5-2x/3 | | 75.0+0.10x=400 | | 18(20+y)= | | -4=-2y+10x | | 1.8C+32=97.7 | | 75.00+.10x=40 | | 18y+360= | | 75.00+10x=400 | | -x+(-x)+(-x)+(-x)= | | 110+23+x=2 | | 2x^2-3x-11x=6 | | 18r^3+33r^2-30r=0 | | -6(v+4)+2v+6=8v+9 | | -5y=2+(-7y) | | 0.8x-4.4=2 | | (9x-20)/(x^2-5x) | | -2(3s-6)-12=-3(8s+1)-4 | | 5/16=z-7/16 | | -2(3s-6)-12=-3(8s+1)+4 | | 12[f+3]=3f | | -3y+1=8 | | 4(y+2)= | | 3.5*5= | | -3v+15=0 | | 5(14+x)= |